ABA-dependent salt and drought stress improve strawberry fruit quality. (15th January 2019) - Perin, Ellen Cristina; da Silva Messias, Rafael; Borowski, Joyce Moura; Crizel, Rosane Lopes; Schott, Igor Bulsing; Carvalho, Ivan Ricardo; Rombaldi, Cesar Valmor; Galli, Vanessa
Highlights: Mild salt and drought stress improve strawberry fruit functional quality. ABA metabolism and of its derivatives was affected by mild salt (SS) and drought (DS) stresses. The mild stress applied did not reduce fruit yield. Application of mild DS and SS may serve as an effective strategy to improve functional quality. Abstract: Strawberry crop is very sensitive to osmotic stress conditions. We investigated the effect of the stress induced by mild drought (DS) and salt (SS) stresses, on molecular, physiological, and metabolic processes in the strawberry crop ( Fragaria ananassa ), cv. Camarosa. The results showed that the fruit yield was not affected. Mild DS and SS also resulted in an increased content of phenolics, anthocyanins, and l -ascorbic acid, and an increased antioxidant activity. These effects were accompanied by increased levels of ABA and its derivatives (phaseic and dehydrophasic acids), alongside the upregulation of several genes involved on their synthesis. Therefore, the results obtained in this study suggest that mild DS and SS improve the functional quality of strawberry fruits through and ABA-dependent mechanism.